Group Counseling: A Method to Increase Motivation at University Student - Lanjar Mustikaningwang; Zulkipi Lessy (Institut Agama Islam Negeri Jember, 2022)
The motivational factor is very significant for every individual in carrying out various activities, such as in the academic field where one of them is in University which requires commitment from undergraduate students to reach academic achievement, by continuing to foster internal motivation within themselves. The purpose of this research is to find out whether group counseling is effective enough in increasing internal motivation in undergraduate students for academic achievement. This study uses a mix-method in data analysis, namely the follow-up explanation model approach, where qualitative data collection is required to explain the results of quantitative research data. The results from the motivation scale (Achievement Motivation Scale) which was carried out during the pre-test before the intervention in the form of post-test group counseling after group counseling showed that there was an increase in the score, and based on the SPSS data analysis, the probability value was obtained. 0.021 and the value <0.05, then Ho is rejected, thus having the same conclusion as the above calculation. Then the qualitative data collection was taken during group counseling with the interview and observation method where it was found that the subjects in this study had various reasons why they got low academic results as evidenced by the cumulative grade point index they got included in the low category, namely <2.50 of a scale of 4.00.